Una mirada desde el orden implicado, la similitud y la diferencia sobre Cierto azul: improvisación armónica para la educación en libertad - Calvo Oviedo, Marlen (2016)
This work aims to approach the recently-published book by Costa Rican author Fernando Contreras Castro, Certain blue (2009). With that in mind, we chose to raise the possibility that, from the magic of the childhood, barriers are broken through implied order that separate the communication between species. This when it happens shows the totality of the relation of the boy with the nature, represented by the cats, and of course with the universe as a totality, its context and music; that is to say, the harmony, which is obtained essentially because the boy has not been programmed by the explained order.Arthur, who is blind and was abandoned by his peers, is educated by six jazz cats, the difference, who offer him a hopeful vision of the human, the resemblance, and a life education, full of creativity.